Functional sparing surgery policy for giant vestibular schwannomas. (15th June 2020) - Bretonnier, Maxime; Bernard, Florian; Tinois, Julien; Troude, Lucas; Cebula, Hélène; Godey, Benoit; Morandi, Xavier
Abstract: Objective: The objective of this study was to compare the tumour control and facial nerve outcome according to the therapeutic strategy, that is extent of resection and post‐operative radiotherapy. Design: Retrospective study of patients with a giant vestibular schwannoma surgically treated from 4 academic skull base centres. Setting: Extent of resection, neurological complications, facial nerve function, MRI follow‐up and occurrence of complementary treatment were reviewed. Participants: Sixty patients were included from 2000 to 2018. Main outcome measures: Primary end points were comparison the tumour control rate and the post‐operative House‐Brackmann grade at last follow‐up according to the extent of tumour removal ( ie total or subtotal removal). Secondary end points were assessment risk factors of poor facial nerve function and comparison complication rate according to extent of tumour removal. Results: Sixty patients had initial surgery at diagnosis. A total resection was realised in 21 cases and a subtotal resection in 39 cases. Thirteen patients needed further treatment. One patient had a recurrence and needed a second surgery 108 months after the initial total resection surgery. Twelve patients underwent post‐operative radiotherapy, for an evolutive residual tumour. Tumour control was more successful in the total resection group (log‐rank test, P  = .015). There was no tumour recurrence after post‐operative radiotherapy. The facial nerve outcome was significantly better in the subtotal resection group (Mean House‐Brackmann grade at last follow‐up: 2.2 ± 1.9) than in the total resection group (House‐Brackmann grade: 3.5 ± 2.2) ( P  = .033). Vestibular schwannoma with a cystic component had better facial nerve outcome ( P  = .0082). Other than facial paralysis, neurological complications were observed in six patients (10% of patients): lower cranial nerves dysfunction in five cases and hemiparesis in one case. Conclusions: Subtotal resection of giant vestibular schwannomas leads to favourable tumour control and facial nerve function and therefore seems to be a valuable strategy.